Teologi Gender dalam Tradisi Sibaliparri: Peran Perempuan Pesisir Polewali Mandar (The Gender Theology in the Sibaliparri Tradition: the Role of Coastal Women in Polewali Mandar) - Indrawati Indrawati; Abdullah Abdullah; Aksa Aksa (Institut Agama Islam Negeri (IAIN) Manado, 2021)
ABSTRACT This article aims to explain the concept of gender theology in the sibaliparri tradition by looking at the role of coastal women in Polewali Mandar Regency. This paper focuses on three main issues, namely the history of the sibaliparri tradition, the role of coastal women in the sibaliparri tradition and the masterminds that influence the role of coastal women in the Sibaliparri tradition in Polewali Mandar Regency. The method used is descriptive qualitative, by interpreting data and facts discovered on the local community. Data collection techniques are field studies, interviews, manuscript studies by examining books, journals, and other forms of literature. This study shows that the history behind the word sibaliparri according to Mandar O'Dianda O'Dibisa's lontara has occured since the reign of Maradiaq Balanipa I Manyambungi and during the reign of Maradiaq IV Kakanna I Pattang Daetta Tommuane sibaliparri has spread throughout the Ammaradia Balanipa region. Later, the coastal women in the current concept of sibaliparri are not only in the domestic area, taking care of the family and reproduction, conceiving and giving birth to children, but also playing a role in the public sphere. The factors that influence coastal women according to the sibaliparri concept include economic, social, cultural and gender issues. In Islamic theology the role of women in various activities is in accordance with Islamic teachings. The existence of Mara'dia continues to play its role in the social life of the community providing the government partners in embodying peace in a synergistic relationship to create a peaceful society. Keywords: Gender Theology, Sibaliparri Tradition, The Role of Women, Polewali MandarABSTRAK Artikel ini bertujuan menjelaskan tentang konsep teologi gender dalam tradisi sibaliparri dengan melihat peran perempuan pesisir di Kabupaten Polewali Mandar. Tulisan ini menjawab tiga masalah pokok yaitu sejarah tradisi sibaliparri, peran perempuan pesisir dalam tradisi sibaliparri dan aktor yang memengaruhi peran perempuan pesisir dalam tradisi Sibaliparri di Kabupaten Polewali Mandar. Metode yang digunakan adalah deskriptif kualitatif, dengan menafsirkan data dan fakta berdasarkan masyaraka setempatt. Teknik pengumpulan data yaitu studi lapangan, wawancara, studi naskah dengan menelaah buku-buku, jurnal, dan bentuk literatur lainnya. Penelitian ini menunjukkan, bahwa sejarah penamaan kata sibaliparri berdasarkan lontara Mandar O’Dianda O’Dibiasa sudah muncul sejak masa pemerintahan Maradiaq Balanipa I Manyambungi dan masa pemerintahan Maradiaq IV Kakanna I Pattang Daetta Tommuane sibaliparri sudah meluas di seluruh wilayah Ammaradia Balanipa. Kemudian Perempuan pesisir dalam konsep sibaliparri saat ini tidak hanya wilayah domestik, mengurus keluarga dan reproduksi mengandung dan melahirkan anak tetapi juga berperan di wilayah publik. Faktor-faktor yang memengaruhi perempuan pesisir menurut konsep sibaliparri di antaranya faktor ekonomi, sosial, budaya dan isu gender. Dalam teologi Islam bahwa peran perempuan dalam berbagai aktivitas adalah sesuai dengan ajaran Islam. Keberadaan Mara’dia menjadi tetap eksis memainkan perannya dalam kehidupan sosial masyarakat sehingga pemerintah memiliki mitra mewujudkan ketentraman dalam hubungan sinergisitas untuk mewujudkan masyarakat yang damai.Kata kunci: teologi gender; tradisi Sibaliparri; peran perempuan; Polewali Mandar